Fatty acid variation in three-spined stickleback (Gasterosteus aculeatus) - Lewis, Henry (2023)
Omega-3/omega-6 long-chain polyunsaturated fatty acids, particularly EPA and DHA, are key biological molecules necessary for growth, survival and reproduction. Environmental heterogeneity in the dietary availability of these compounds across aquatic environments has resulted in differential evolution of traits associated with DHA biosynthesis among populations of the same species exploiting divergent resources. Such disparities in DHA biosynthetic capacities have resulted in population-level differences in omega-3/omega-6 long-chain polyunsaturated fatty acid phenotypes. Here, fatty acid profiles of three-spined stickleback ecotypes inhabiting or originating from lochs on North Uist drastically differing in environmental parameters, notably pH and nutrient conditions, were measured to understand how EPA, DHA and total fatty acid concentrations differ between distinct environments. To support any conclusions drawn from corresponding results, a summary analysis on algal EPA and DHA contents was performed to showcase fatty acid resource heterogeneity between aquatic habitats. Moreover, fatty acids of plankton sampled from an acidic and alkaline loch were profiled to understand how the dietary availability of polyunsaturated fatty acids varies between analysed freshwater environments. Algae EPA and DHA contents were significantly influenced by habitat and taxonomy. Furthermore, significant differences were discovered between loch plankton in concentrations of all analysed polyunsaturated fatty acids, suggesting divergent selection pressures may act on corresponding freshwater stickleback populations. Finally, EPA, DHA and total fatty acid concentrations significantly varied between lochs, ecotypes and sexes. Results were used to predict divergent metabolic evolution between three-spined stickleback populations.